MEKANISME PEMUNGUTAN SUARA PEMILIHAN KEPALA DAERAH DENGAN CALON TUNGGAL PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 100/PUU-XIII/2015 - Adriana, Adriana; Rizqiawan, Rizqiawan (Res Publica: Jurnal Hukum Kebijakan Publik, 2017)
The local elections with a single candidate elections to elect regional heads who followed only one pair of candidates only / single candidate. This study aims to determine how the voting mechanism in the implementation of the local elections with a single candidate against the order of the Constitutional Court Number 100 / PUU-XIII / 2015. In this  study the authors will solve the problem regarding the enactment of a new voting mechanism in the implementation of the local elections with a single candidate. This research is a normative legal or commonly called the doctrinal legal research done by researching library materials or secondary data consists of primary legal materials, secondary law and tertiary legal materials. Primary legal materials consist of legislation, notes the official records, the minutes in the making of legislation and the decision of the judge's decision. As for the secondary law in the form of all the publicity about the law which is not an official documents. The results of research and discussion to explain that after the decision of the Constitutional Court Number 100 / PUU-XIII / 2015 there is a new mechanism of voting in local elections with a single candidate by selecting "agree" or "disagree" on a single candidate head area.